Podolian Melting Pot: Formation of Multicultural Community of Nobles on the Eastern Border of Polish Kingdom of the Fifteenth Century Europe - Mykhaylovskiy, V. (Український історичний журнал, 2020)
The purpose of this study is to present the ways of multicultural noble community formation on the territory of Podillia (Podillya), and starting from 1434 – of Podolian voivodeship, which was the easternmost province of Polish Kingdom at the time. The research methodology follows the principles of systematizing the materials and applying interdisciplinary lenses. It utilizes a number of general methods of historical studies: historiographical, terminological, biographical, prosopographical, genealogical, and linguistic analysis. Based on the analysis of probable sites of origin of the nobles who received land assignations on the territory of Podolian voivodeship under the rule of Władysław III in 1434–1444, the study traces specific regions in Polish and Czech kingdoms, from which the nobles relocated to the eastern border of Europe of that time. The main regions of the incoming to Podolian voivodeship nobles’ origin include Lesser Poland, Greater Poland, Mazowia, Moravia, and Silesia. The farthest site of origin of these nobles were Moravia and Wieluń district of Sieradz voivodeship in Greater Poland. The rest of the sites of origin, which can be identified, lie at the 500 to 700 kilometre distance from Podillia. For the period of the 15th century, the study differentiates several ethnic and socio-professional groups that added to the noble Podolian community. These are mercenaries, coming mostly from the territory of Czech Kingdom where the Hussite War was coming to an end at the time, who pursued noble titles by means of military service. In the middle and during the second half of the 15th century the majority of "new Podolians" settled in Podillia and already in the 2nd and 3rd generations were considered native in the local noble community. Conclusions. Determination of the probable places of origin of the nobiles incoming to the territory of Podillia in the 15th century demonstrates that they were coming from practically all the regions of the Polish Kingdom. Military people became quite a distinguished group in Podillia. The Polish king’s inability to supply the military with his own subordinates made him draft people coming mostly from the Czech Kingdom. A share of them stayed in Podillia after completing their service. It is notable that at the time there was a possibility to change their social status and use the privileges granted through military service to become nobles. Мета дослідження полягає у представленні шляхів формування мультикультурної шляхетської спільноти на території Поділля (від 1434 р. Подільського воєводства), яке була найсхіднішою провінцією Польського королівства. Дослідницька методологія базується на принципах системності та міждисциплінарності. Використано такі загальноісторичні методи: історіографічний, термінологічний, біографічний, просопографічний, генеалогічний та лінґвістичного аналізу. У дослідження на підставі аналізу ймовірних місць походження шляхтичів, що отримували земельні надання на території Подільського воєводства за правління Владислава III у 1434–1444 рр., показано реґіони Польського й Чеського королівств, звідки вони переселялися на східний кордон тогочасної Європи, а саме Малопольща, Мазовія, Великопольща, Моравія, Силезія. Найвіддаленішим місцем, звідки походили ці шляхтичі, були Моравія та Велюнський повіт Cерадзького воєводства у Великопольщі. Решта місць походження, які можна локалізувати, віддалені від Поділля на 500–700 км. Для другої половини XV ст. виділено кілька етнічних і соціопрофесійних груп, з яких поповнювалася подільська шляхетська спільнота. Це військові найманці, що походили насамперед із території Чеського королівства, де на той час завершилися Гуситські війни. У середині та другій половині XV cт. більшість із «нових подолян» осіла на Поділлі, а у другому і третьому поколіннях уже вважалися своїми в місцевій шляхетській спільноті. Висновки. З’ясування ймовірних місць походження прибулої у XV cт. на територію Поділля шляхти показує, що походила вона практично з усіх реґіонів Польського королівства. Помітною групою на Поділлі у той час стали військові. Неможливість польського короля забезпечити військо своїми підданими змушувала наймати вихідців із Чеського королівства. Частина з них після завершення служби осідала на Поділлі. Також у той час існувала можливість зміни соціального статусу для міщан, котрі завдяки військовій службі могли стати шляхтичами.